In Vitro Conditioned Bone Marrow-Derived Mesenchymal Stem Cells Promote De Novo Functional Enteric Nerve Regeneration, but Not Through Direct-Transdifferentiation. (29th September 2015) - Lin, Rong; Ding, Zhen; Ma, Huan; Shi, Huiying; Gao, Yuanjun; Qian, Wei; Shi, Weina; Sun, Zhaoli; Hou, Xiaohua; Li, Xuhang
Abstract : Injury or neurodegenerative disorders of the enteric nervous system (ENS) cause gastrointestinal dysfunctions for which there is no effective therapy. This study, using the benzalkonium chloride-induced rat gastric denervation model, aimed to determine whether transplantation of bone marrow-derived mesenchymal stem cells (BMSC) could promote ENS neuron regeneration and if so, to elucidate the mechanism. Fluorescently labeled BMSC, isolated from either WT (BMSC labeled with bis-benzimide [BBM]) or green fluorescent protein (GFP)-transgenic rats, were preconditioned in vitro using fetal gut culture media containing glial cell-derived neurotrophic factor (GDNF), and transplanted subserosally into the denervated area of rat pylorus. In the nerve-ablated pylorus, grafted BMSC survived and migrated from the subserosa to the submucosa 28 days after transplantation, without apparent dedifferentiation. A massive number of PGP9.5/NSE/HuC/D/Tuj1-positive (but GFP- and BBM-negative) neurons were effectively regenerated in denervated pylorus grafted with preconditioned BMSC, suggesting that they were regenerated de novo, not originating from trans-differentiation of the transplanted BMSC. BMSC transplantation restored both basal pyloric contractility and electric field stimulation-induced relaxation. High levels of GDNF were induced in both in vitro-preconditioned BMSC as well as the previously denervated pylorus after transplantation of preconditioned BMSC. Thus, a BMSC-initiated GDNF-positive feedback mechanism is suggested to promote neuron regeneration and growth. In summary, we have demonstrated that allogeneically transplanted preconditioned BMSC initiate de novo regeneration of gastric neuronal cells/structures that in turn restore gastric contractility in pylorus-denervated rats. These neuronal structures did not originate from the grafted BMSC. Our data suggest that preconditioned allogeneic BMSC may have therapeutic value in treating enteric nerve disorders. Stem Cells   2015;33:3545–3557